Development of a Video Game for Cognitive Stimulation in Early-Stage Alzheimer's Disease (2024)
In this research, a videogame was developed using Unity and WebGL as a cognitive stimulation strategy for patients with early-stage Alzheimer's disease. The process of construction of the videogame, began with the definition of cognitive needs and patient characteristics, obtained through literature review and interviews with experts. The interviews were focused on the following skills: the memory, the attention, the executive function, and the problem solving. These skills can be positively impacted with videogames and are detailed according to their degree of impairment in Alzheimer's disease.Next, the story and conceptual methodology of the videogame were identified with a literature review: achieving a certain degree of personalization according to the patient's context, inclusion of rhythmic music that accompanies the player's experience, and adaptation of different difficulty levels based on each patient. The videogame is conceptually categorized as a Serious Game and was created with a Game Design Document (GDD) specifying the dynamics and mechanisms of the game. Following, the video game was development using Unity and WebGL framework.The video game starts with the player entering the mini world, placing the user in the scenario of the initial route, which aims to perform a basic diagnosis of the player's weakest skills. After, the central cycle begins, which involves exploring the world in search of mini games that can be either completed or failed. Completing all the mini games in the scenario is unlocked.Based on the psychiatrist's indications with respect to the validation of previous tools, the reco